2011
DOI: 10.1021/bi101796m
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Structural Roles of Residues in the Third Extramembrane Segment of Adrenal Cytochrome b561

Abstract: Several residues in the third extramembrane segment (EM3) of adrenal cytochrome b561 have been proposed to be involved in this cytochrome’s interaction with ascorbate, but there has been no systematic evaluation of residues in the segment. We used alanine-scanning mutagenesis to assess the functional and structural roles of the EM3 residues and several adjacent residues (residues 70–85) in the bovine cytochrome. Each alanine mutant was expressed in a bacterial system, detergent solubilized, and affinity purifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 37 publications
2
8
1
Order By: Relevance
“…Furthermore, and also in contrast to our results for both paralogs, the electron acceptance of Zm -Y71F was accelerated . A comparable change in the α-band shape as seen for A-Y69F in this study has been shown for the corresponding Bt Cyt b 561 -CG variant Y73A as well as for the variant K85A (corresponds to A-K80), whereupon the authors suggested a cation−π-type interaction , between those amino acids based on a bioinformatic model. , …”
Section: Discussioncontrasting
confidence: 83%
See 3 more Smart Citations
“…Furthermore, and also in contrast to our results for both paralogs, the electron acceptance of Zm -Y71F was accelerated . A comparable change in the α-band shape as seen for A-Y69F in this study has been shown for the corresponding Bt Cyt b 561 -CG variant Y73A as well as for the variant K85A (corresponds to A-K80), whereupon the authors suggested a cation−π-type interaction , between those amino acids based on a bioinformatic model. , …”
Section: Discussioncontrasting
confidence: 83%
“…14 A comparable change in the α-band shape as seen for A-Y69F in this study has been shown for the corresponding BtCytb 561 -CG variant Y73A as well as for the variant K85A (corresponds to A-K80), 45 whereupon the authors suggested a cation−π-type interaction 46,47 between those amino acids based on a bioinformatic model. 38,45 BtCytb 561 -CG exhibits 31.7% and 33.8% sequence identity with the A-and B-paralogs, respectively, and Zmcytb561 exhibits values of 63.5% and 39.7%, respectively. Should a proton-coupled electron transfer (PCET) be active in CYBASC proteins, as proposed for Btcytb 561 -CG 16,48 and Zmcytb 561 , 5,49 the conserved tyrosine residue is possibly involved in this process by proton transfer to one of the heme b-coordinating histidine residues.…”
Section: ■ Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…They have a unique structure including six hydrophobic transmembrane α-helices being bound with two heme b prosthetic groups [ 1 , 2 ]. The redox potential measurements for the purified proteins indicated that the cytosolic ascorbate is the electron donor for the CYB561 proteins [ 3 , 4 ]. Furthermore, some members of CYB561 showed a distinct ferric reductase activity that could have a vital role for the iron metabolism of eukaryotic cells [ 5 ].…”
Section: Introductionmentioning
confidence: 99%